(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Objective: The objective of present study is to evaluate the potential of liquisolid (LS) technology to enhance the dissolution characteristics of a combination of two poorly soluble drugs formulated as a single tablet. Materials and Methods: LS compacts have been prepared using compositions with varying ratios of propylene glycol (as water miscible non-volatile vehicle), lactose, and microcrystalline cellulose PH 102 (MCC PH 102) (as carriers), while Syloid® 244FP silica as a coating material. To evaluate the role of additives on various parameters such as loading factor, powder flow, disintegration, and dissolution profile of prepared LS formulations, number of additives such as Kollidon® 30, hydroxy propyl methyl cellulose-low viscosity, polyethylene glycol 4000, Kollidon® VA64, and low-substituted hydroxypropyl cellulose-LH-11 were added to the formulation. Results and Discussion: Among the tested carriers, MCC PH 102 was found to enhance drug release considerably. Addition of additives was found to further enhance powder flow and provide faster release of drugs from formulations. Among all the LS formulations prepared, LS - 18 demonstrated the fastest disintegration time (1.02 min) and fastest dissolution rate (84.6% in 10 min for glipizide and 44.6% for atorvastatin) with 100% drug release. Conclusion: The study demonstrated that LS technology can lead to suitable coformulation of two poorly soluble drugs for antidiabetic-antihyperlipidemic cotherapy of metabolic syndrome with enhanced dissolution.